Accelerating Women-Owned MSMEs Through Digital Financial Literacy, Bookkeeping Adoption, and E-Commerce - Hamdani Hamdani; Eni Suharti; Suryadi Suryadi; Andini Ekasari; Noorkartina Mohamad (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Women-owned MSMEs in Balaraja continue to face challenges in financial recording, digital financial management, and access to wider online markets. These limitations reduce their ability to manage cash flow, strengthen business credibility, and improve business sustainability. Contribution: Development of an integrated empowerment acceleration model that combines financial literacy, digital bookkeeping adoption, and e-commerce utilization to strengthen the sustainability and competitiveness of women-owned MSMEs. Method: This community service program implemented an integrated empowerment model through training, digital tool development, and structured mentoring. A total of 55 women-owned MSMEs participated in the training stage, while 22 selected MSMEs continued to the implementation and mentoring stage. Results: The program significantly improved participants’ knowledge, digital financial literacy, and digital business practices. Knowledge scores increased from 56% to 78% and from 60% to 85% across the two stages, while digital financial literacy scores rose from 64% to 76% and from 66% to 82%. Online market expansion improved from 20% to 50%, the Empowerment Index increased by 22.57%, and average turnover rose by 12%. Conclusion: The findings indicate that women-owned MSME empowerment becomes more effective when digital financial literacy is integrated with bookkeeping tools, e-commerce facilities, and continuous mentoring.